Defining the Epidemiology and Burden of Severe Respiratory Syncytial Virus Infection Among Infants and Children in Western Countries - Bont, Louis (Infect Dis Ther, 2016)
INTRODUCTION: The REGAL (RSV [respiratory syncytial virus] Evidence—a Geographical Archive of the Literature) series provides a comprehensive review of the published evidence in the field of RSV in Western countries over the last 20 years. This first of seven publications covers the epidemiology and burden of RSV infection. METHODS: A systematic review was undertaken for articles published between Jan 1, 1995 and Dec 31, 2015 across PubMed, Embase, The Cochrane Library, and Clinicaltrials.gov. Studies reporting data for hospital visits/admissions for RSV infection among children (≤18 years of age), as well as studies reporting RSV-associated morbidity, mortality, and risk factors were included. Study quality and strength of evidence (SOE) were graded using recognized criteria. RESULT: 2315 studies were identified of which 98 were included. RSV was associated with 12–63% of all acute respiratory infections (ARIs) and 19–81% of all viral ARIs causing hospitalizations in children (high SOE). Annual RSV hospitalization (RSVH) rates increased with decreasing age and varied by a factor of 2–3 across seasons (high SOE). Studies were conflicting on whether the incidence of RSVH has increased, decreased, or remained stable over the last 20 years (moderate SOE). Length of hospital stay ranged from 2 to 11 days, with 2–12% of cases requiring intensive care unit admission (moderate SOE). Case-fatality rates were <0.5% (moderate SOE). Risk factors associated with RSVH included: male sex; age <6 months; birth during the first half of the RSV season; crowding/siblings; and day-care exposure (high SOE). CONCLUSION: RSV infection remains a major burden on Western healthcare systems and has been associated with significant morbidity. Further studies focusing on the epidemiology of RSV infection (particularly in the outpatient setting), the impact of co-infection, better estimates of case-fatality rates and associated risk factors (all currently moderate/low SOE) are needed to determine the true burden of disease. FUNDING: Abbvie. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s40121-016-0123-0) contains supplementary material, which is available to authorized users.